Compensatory growth in Yankasa lambs. 2. Carcass Composition - Lakpini, C.A.M.; Adu, I.F.; Buvanendran, V.; Umunna, N.N. (1983)
22 yankasa lambs were slaughtered, jointed and dissected after a 184-day feeding experiment involving 4 planes of nutrition: High-high, (HH) high-low (HL), Low-high (LH) and Low-low (LL). Part of the results of the feeding experiment have been reported by lakpini et al. (1982). The carcass weights of HH and HL animals were 1.2 times higher than those of animals on LH and LL treatments respectively. The dressing percentage, percents total fat and total muscle were higher in the high protein ration than in the low protein ration. Animals on HH treatment had 4.5% more total fat than LH animals while HL animals had 3.1% more total fat than the LL group. Also, relative to the carcass weight, the LH animals had more muscle than the HH group. Thus, the LH animals proportionately had more muscle and less fat than the animals on HH treatment. Percentage total muscle and total fat were higher in the males than in the female animals. It is concluded that irrespective of the nutritional regime to which an animal is subjected, the cuts and components of its carcass will be in definite proportions to its liveweight.